1997
DOI: 10.2337/diab.46.11.1799
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Muscle Insulin and Glucose Levels in Normal and Insulin-Resistant Zucker Rats

Abstract: To study interstitial insulin and glucose concentrations, microdialysis was performed in the medial femoral muscles in normal SD rats as well as in insulin-resistant obese Zucker rats during a euglycemic insulin clamp. [14C]inulin was given (0.1 mCi/rat) as a constant subcutaneous infusion 24 h before the insulin clamp. Insulin infusion rates were 5-8 mU x kg(-1) x min(-1) (low rate) for 140 min and 10-20 mU x kg(-1) x min(-1) (high rate) for another 100 min. The relationship between insulin and [14C]inulin di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 17 publications
(33 reference statements)
10
46
0
Order By: Relevance
“…Our data, obtained in experiments where each animal serves as its own control, suggest that compensation in terms of higher interstitial concentrations of glucose might already occur at physiological insulin concentrations but that this it not enough to overcome the reduction in glucose uptake. The microdialysis technique used here was validated recently in the rat muscle and was shown not to alter either the capillary permeability or interstitial fluid concentration of either glucose or insulin [26,27]. In our study (data not shown), the constant dialysis recovery of inulin and retrodialysis of labelled glucose ascertained constant and steady state microdialysis conditions throughout the study.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Our data, obtained in experiments where each animal serves as its own control, suggest that compensation in terms of higher interstitial concentrations of glucose might already occur at physiological insulin concentrations but that this it not enough to overcome the reduction in glucose uptake. The microdialysis technique used here was validated recently in the rat muscle and was shown not to alter either the capillary permeability or interstitial fluid concentration of either glucose or insulin [26,27]. In our study (data not shown), the constant dialysis recovery of inulin and retrodialysis of labelled glucose ascertained constant and steady state microdialysis conditions throughout the study.…”
Section: Discussionsupporting
confidence: 59%
“…Insulin resistance could be induced by high glucose concentrations ambient to the cells through formation of hexosamines, interfering directly with the insulin signal transduction. Also, it is notable that the insulin-resistant Zucker rat has higher than normal glucose concentrations in muscle interstitial fluid even under normoglycaemic insulin clamping conditions [27]. In contrast to the decrease in A-I concentration difference for glucose, the lactate I-A concentration difference increased during epinephrine exposure.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations